The Mediating Role of Coping Styles on Impulsivity, Behavioral Inhibition/Approach System, and Internet Addiction in Adolescents From a Gender Perspective - Li, Qi; Dai, Weine; Zhong, Yang; Wang, Lingxiao; Dai, Bibing; Liu, Xun (Frontiers in Psychology, 2019)
Previous findings have shown that impulsivity and Behavioral Inhibition/Approach System (BIS/BAS) have substantial effects on adolescents’ Internet addiction, but the mechanisms underlying these associations and gender differences in these effects have received little attention. We examined the mediating effects of coping styles from impulsivity, and BIS/BAS to Internet addiction as well as gender differences in these associations. A total of 416 Chinese adolescents were examined using a cross-sectional survey involving Young’s Diagnostic Questionnaire for Internet Addiction, Barratt Impulsiveness Scale, BIS/BAS scales, and Coping Style Scale for Middle School Students. The data were analyzed using the independent sample t-test, chi-square test, Pearson correlation, and structure equation modeling. The results from the multiple-group (by adolescent gender) structural model analysis revealed that both impulsivity (p < 0.001) and BIS (p = 0.001) directly predicted positive Internet addiction in girls, while both impulsivity (p = 0.011) and BAS (p = 0.048) directly predicted positive Internet addiction in boys. Furthermore, emotion-focused coping mediated the relationship between impulsivity and Internet addiction (β = 0.080, 95% CI: 0.023-0.168) and the relationship between BIS and Internet addiction (β = 0.064, 95% CI: 0.013-0.153) in girls, while in boys, problem-focused coping and emotion-focused coping mediated the association between impulsivity and Internet addiction (β = 0.118, 95% CI: 0.031-0.251; β = 0.065, 95% CI: 0.010-0.160, respectively) and problem-focused coping mediated the association between BAS and Internet addiction (β = -0.058, 95% CI: (-0.142)–(-0.003)). These findings extend our insight into the mechanisms underlying the associations among impulsivity, BIS/BAS, and Internet addiction in adolescents and suggest that gender-sensitive training approaches to decrease adolescents’ Internet addiction are indispensable. These interventions should focus on the different gender predictors of adolescent Internet addiction and on the development of specific coping styles for boys and girls respectively.